Analisis Pengendalian Persediaan Bahan Baku Bakpia dengan Sistem Min-Max untuk Efisiensi Biaya Persediaan pada UD. ABC - Fanny Setiawan; Herlina Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD. ABC is a bakpia producer located in Gempol, Pasuruan. The problem often experienced by producers with this make-to-stock system is the occurrence of excess and shortage of raw materials due to meeting unstable customer demand. This condition causes increased inventory costs, so more effective control efforts are needed. This study aims to reduce total inventory costs through the application of the min-max stock method. The research stages carried out include forecasting demand for the next 3 months to meet the amount of raw material requirements using the weighted moving average method, followed by determining safety stock, reorder points, and minimum and maximum stock limits. Then comparing the total inventory costs between the existing conditions and the proposed min-max method. The results of this study show that the application of the min-max stock method successfully reduced total inventory costs from Rp 10,296,672 to Rp 5,065,997, with an efficiency value of 51%. This method has proven effective as an inventory control solution in fluctuating demand conditions.